Impact of the European Private Law Codification outside Europe I: Common Law in the Old Colonial Empire (Pakistan) - Hassan, Amna (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2020)
The paper provides insight into the existence of codified private law in a Common law colony – Pakistan – outside the realm of Europe. As the Britain ruled the subcontinent for a long period of time, therefore, Pakistan continued to follow the Common law system regulated by their British colonizers. It gives a detailed account of the existence and application of common law in the subcontinent, and on the intent of the British to codify the laws in the region to accomplish their ‘divide and rule’ policy for the administration of the subcontinent. Using this as the proverbial measuring stick, the paper then seeks to justify a parallel system of codified private laws in existence in Europe, in a compact manner. Not only this, the paper also reflects upon the impact of the codified private law in the legal development of Pakistan as a whole till to date. For that purpose, an explanatory over-view of the Indian Contract Act of 1872 is provided including the history, traditional and common law roots, and the Act, itself.